Las contribuciones de Finn Kydland y Edward Prescott a la macroeconomía dinámica: la consistencia temporal de la política económica y las fuerzas motrices detrás de los ciclos económicos - Kydland , Finn (2020)
In 2004, Finn Kydland and Edward Prescott won the Bank of Sweden Prize in Economic Sciences, in memory of Alfred Nobel, for their key contributions in two closely related areas of macroeconomic research. The first of them has to do with the design of economic policy. Kydland and Prescott discovered inherent imperfections - credibility problems - in the ability of governments to implement desirable economic policies. The second contribution is related to fluctuations in business cycles. Kydland and Prescott demonstrated how variations in technological development, the main source of growth in the long term, can cause short-term fluctuations. Thus, this work became a new Operative paradigm for macro analysis based on microeconomic foundations. The work of Kydland and Prescott has transformed academic research in HEconomy; Furthermore, it has had a great impact on macroeconomic analysis and economic policy decision-making.